RETRACTED: SHP2 improved Late-onset fetal growth restriction via modulating ROS/BRD4/PI3K/YAP/PIGF signaling induced angiogenesis - Fang Li; Yaqin Li; Wei Hao; Xuan Zhang; Xueyan Shen; Botao Yang; Wei Zhang; Liman Fu; Suyan Gu (PLoS ONE, 2026)
Objective To look into the molecular processes and function of SHP2 in late-onset fetal growth restriction (LO-FGR). Methods An elaborate research technique included in vitro experiments and bioinformatics analysis. By identifying differentially expressed genes (DEGs) and enriched pathways linked to fetal growth restriction (FGR), the bioinformatics analysis of the GSE147776 dataset offered first insights into putative signaling networks, such as angiogenesis and oxidative stress. This bioinformatic information served as a guide for in vitro investigations using endothelial progenitor cells (EPCs) grown under circumstances similar to LO-FGR. EPCs were divided into six groups based on different drug treatments: NC group, Model group, Model + JQ-1 group, Model + JQ-1 + PHPS1 group, Model + JQ-1 + PHPS1 + 740Y-P group, and Model + JQ-1 + PHPS1 + 740Y-P + Verteporfin group. Using Western Blot analysis, the regulatory function of SHP2 in the ROS/BRD4 and PI3K/YAP/PIGF pathways was examined. We investigated the impact of SHP2 on the angiogenic potential of EPCs using tube formation assays and Western Blot analysis.Using Western Blot, colony formation assays, and flow cytometry to identify cell cycle progression and death, the mechanism by which SHP2 alleviates delayed fetal development limitation was investigated. Results 207 DEGs were found to be considerably enriched in the Hedgehog and Hippo signaling pathways, according to a bioinformatics study of the FGR dataset GSE147776. It’s interesting to note that SHP2 correlated positively with PI3K, CREB, and YAP and negatively with BRD4, NOX2, and P53. Under conditions akin to the in vivo LO-FGR environment, NOX4 and nuclear BRD4 protein expression dramatically rose, whereas p-SHP2, p-PI3K, nuclear YAP, Nrf2, PIGF, VEGF, HIF1α, OCT4, SOX2, and C-Myc protein expression greatly decreased. EPC proliferation was markedly reduced, the G2 phase of the cell cycle decreased, and apoptosis increased. After treatment with the BRD4 inhibitor JQ-1, the expression of NOX4 and nuclear BRD4 proteins significantly decreased, while the expression of p-SHP2, p-PI3K, nuclear YAP, Nrf2, PIGF, VEGF, HIF1α, OCT4, SOX2, and C-Myc proteins increased. EPC proliferation increased, the G2 phase of the cell cycle increased, and apoptosis decreased. When SHP2 was inhibited, NOX4 expression increased, while the expression of p-SHP2, p-PI3K, nuclear YAP, Nrf2, PIGF, VEGF, HIF1α, OCT4, SOX2, and C-Myc proteins decreased. EPC proliferation decreased, the G2 phase of the cell cycle decreased, and apoptosis increased. Conclusion SHP2 improves LO-FGR by regulating ROS/BRD4 and PI3K/YAP/PIGF-induced activation of endothelial progenitor cells.